Relevansi Hak Asasi Manusia dalam Pelindungan Pekerja Migran Indonesia - R. Mustar Lofi (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study explores the relevance of human rights in the protection of Indonesian migrant workers (PMI), a pressing issue amid the high incidence of rights violations in destination countries. In the context of globalization and increasing labor mobility, PMI are often subject to exploitation, discrimination, and both physical and psychological violence. Although Indonesia has enacted national laws, such as Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers, and ratified several international human rights instruments, the actual implementation of HR principles in policies and practices remains deficient. This study adopts a normative juridical method, using legislative and literature review approaches. The findings indicate that the current protection mechanisms fail to fully guarantee the basic rights of PMI as outlined in international human rights frameworks. Hence, there is a pressing need for synergy between strengthened national regulations, effective human rights diplomacy, and active civil society involvement in monitoring and advocating PMI rights. This study contributes to the development of HR-based policies and reinforces the urgency of Indonesia’s ratification of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICRMW) as a strategic step toward comprehensive and just protection.